PERBEDAAN PENGETAHUAN, SIKAP,PRAKTIK DAN KEBERADAAN JENTIK SEBELUM DAN SETELAH INTERVENSI PENERAPAN SATU RUMAH SATU JURU PEMANTAU JENTIK DI DESA KOROWELANGANYAR KECAMATAN CEPIRING KABUPATEN KENDAL - Istiqomah Istiqomah; Martini Martini; Lintang Dian Saraswati; Nissa Kusariana (Jurnal Kesehatan Masyarakat (Undip), 2021)
The practice of eliminating mosquito nests (PSN) is carried out by jumantik to reduce dengue fever. Jumantik must be formed starting from each house by appointing one family member as the jumantik (Movement 1 House 1 Jumantik). The jumantik program in the village exists, but it has not been implemented. The purpose of this study was to analyze differences in knowledge, attitudes, community practices and the presence of larvae that were intervened and not intervened by implementing the movement of One House One Jumantik. This type of research is a quasi experimental, with the Nonequivalet Group Design approach. The instruments used in this study were a questionnaire, a larva monitoring checklist, a guidebook. The research sample was 40 people in the experimental group and 40 people in the control group using purposive sampling technique. Analysis of the research data using the Mann Whitney test, Wilcoxon test, Chi square test. The results showed that there were differences in the mean of knowledge (p: 0.001 ≤ α (0.05)), attitudes (p: 0.001 ≤ α (0.05)), and practice (p: 0.002 ≤ α (0.05)) in the group. experimental and control groups before and after the intervention. The presence of larvae before (p: 0.799> α (0.05)), and after the intervention (p: 0.012 <α (0.05)). The mean of knowledge, attitudes, and practices in the experimental group after the intervention was greater than the control group. The intervention carried out by implementing one house and one larva observer can reduce the presence of larvae. Suggestions for the community to be active in the one house one jumantik and for officers to further improve monitoring evaluation for the sustainability of the PSN DHF program.